ANALISIS BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN PADA RESINDA HOTEL KARAWANG - Dinar Mustika Gunawan; Dedi Mulyadi; Sungkono Sungkono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to increase understanding of organizational culture and employee performance. The research method used is a descriptive qualitative method. The dfescriptive qualitative method is a method used by researchers to fine knowledge or theory regarding research at a certain time. Organizational culture is an organization’s value sustem and will influence the way work is done and the way employees behave. Resinda Hotel Karawang is a four star hotel in the city of Karawang. Resinda Hotel Karawang has a 256 rooms. The result of this article is that organizational culture has agood effect on employee performace.